The Current Process for the Recycling of Spent Lithium Ion Batteries - Zhou, Li-Feng; Yang, Dongrun; Du, Tao; Gong, He; Luo, Wen-Bin (Frontiers in Chemistry, 2020)
With the development of electric vehicles (EVs) involving lithium ion batteries (LIBs) as energy storage devices, the demand for LIBs in the whole industry is increasing, which is bound to lead to a large number of LIBs in the problem of waste, recycling and reuse. If not handled properly, it will certainly have a negative impact on the environment and resources. Current commercial LIBs mainly contain transition metal oxides or phosphates, aluminum, copper, graphite, organic electrolytes containing harmful lithium salts and other chemicals. Therefore, the recycling and reuse of spent LIBs has been paid more and more attention by many researchers. However, due to the high energy density, high safety and low price of LIBs have great differences and diversity, the recycling of waste lithium ion batteries has great difficulties. This paper reviews the latest development of the recovery technology of waste lithium ion batteries, including the development of recovery process and products. In addition, the challenges and future economic and application prospects are described.